A Simple Solution for IoT Experimentation in the Context of Future Internet Architectures - Chaib, Ramon P. S.; Alberti, Antonio M. (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF); 2017: Anais do VIII Workshop de Pesquisa Experimental da Internet do Futuro, 2017)
In the last decade, many approaches appeared to revolutionize Internet architecture from scratch. They are collectively called Future Internet Architectures. In this paper, we address the challenge of experimenting with Internet of things in this context. Using open-source tools, we developed a standard scenario capable to evaluate proposals in a small scale first (locally, in laboratory), and latter in large scale cloud-based testing platform. As a use case of the proposal, we discuss its application to the eXpressive Internet Architecture.